CUTE‐CV: A Prospective Study of Enhanced Left Atrial Appendage Visualization with Microbubble Contrast Agent Use during Transesophageal Echocardiography Guided Cardioversion. Issue 9 (11th May 2013) - Bernier, Mathieu; Abdelmoneim, Sahar S.; Stuart Moir, W.; Eifert Rain, Susan (Sue) J.; Chandrasekaran, Krishnaswamy; Ammash, Naser M.; Mulvagh, Sharon L.
<x xml:space="preserve">Abstract</x> Objectives The aim of our study was to demonstrate that the use of contrast microbubbles during transesophageal echocardiography (TEE) guided cardioversion will improve interpretation of the TEE images. Background TEE‐guided cardioversion of atrial flutter or fibrillation (AF) is a safe and proven method to restore sinus rhythm. However, artifacts and dense spontaneous echo contrast in the left atrial appendage (LAA) can sometimes decrease the level of confidence in excluding the presence of thrombus. Methods One hundred patients referred for TEE‐guided cardioversion were prospectively enrolled and microbubble contrast agent (DEFINITY) was administered after the clinical decision had been made regarding suitability for cardioversion. Noncontrast and contrast images were compared during subsequent offline analysis. Results LAA dimensions and contractility indices were higher, artifacts were significantly differentiated, previously unsuspected LAA filling defects were identified, and the level of confidence in excluding thrombus was enhanced in the contrast images when compared to the noncontrast images. After 4 months follow‐up, 1 stroke‐associated death occurred in a patient who had LAA thrombus recognized only by contrast. Left atrial appendage visualization is enhanced with microbubble contrast agent use during transesophageal echocardiography guided cardioversion and is useful in identification of intracardiac thrombus.